Effects of salt-induced degradation on the moisture stability and high-temperature performance of PPA/BF/SBS composite modified asphalt mixture - Huang, Kaike; Wei, Jian; Liang, Xiaodan; Nong, Huangfeng; Xu, Yaoliang; Huang, Linheng (Frontiers in Materials, 2026)
Asphalt pavements in coastal hot and humid regions are perennially affected by salt-induced degradation, which exacerbates moisture damage and aging processes in asphalt mixtures. To enhance the resistance to salt-induced degradation, this study employed polyphosphoric acid (PPA) and chemically modified bagasse fiber (BF) for composite modification of SBS asphalt. A systematic evaluation was conducted on the fundamental characteristics of the PPA/BF/SBS composite modified asphalt and pavement performance of its mixtures. By simulating the actual service environment of coastal pavements, a vibrating salt solution immersion test was designed to investigate the evolution of pavement performance for the PPA/BF/SBS composite modified asphalt mixture under salt-induced degradation environment. Molecular dynamics simulations were further integrated to investigate the asphalt adhesion mechanism. The results indicate that after salt-induced degradation, the penetration of all asphalt samples reduced, while the softening temperature and flow resistance increased. The composite modified asphalt exhibited the smallest changes in properties, demonstrating superior resistance to salt-induced degradation. Based on the performance variations both prior to and following salt-induced degradation, the optimal content was determined as 1.0% PPA + 3% BF. The composite modified asphalt mixture maintained higher residual stability both prior to and following salt-induced degradation, indicating effectively improved moisture and high-temperature stability. Molecular dynamics simulations further revealed that the decline in adhesion energy between PPA/BF/SBS composite modified asphalt and the aggregate in salt solution was less pronounced than that of the SBS asphalt, verifying its enhanced anti-erosion mechanism. Overall, the comprehensive pavement performance of the PPA/BF/SBS composite modified asphalt surpasses that of the SBS asphalt.